Modelling And Study Of Control Structures Of Reactive Distillation For The Production Of Methyl Tert-Butyl Ether (MTBE) - Jeffrey Lee, Jie Yi (Universiti Sains Malaysia, 2021)
This project studies the reactive distillation of methyl tertiary butyl ether (MTBE). A simulation model for this process was selected based on a selected literature source, with additional information utilised from other literature sources. This model was and successfully modelled in the ASPEN PLUS software. After successful running of the simulation, the model in this project was verified with the original source it was based on. After verifying that the model created leads to a result similar to the original reference, the project was moved to the dynamics portion. Controllers were installed using ASPEN Dynamics and their responses to disturbances and set-point changes were evaluated. The controllers FLOWMET, TEMPC and LEVELTOPS were evaluated with step-point changes. These controllers displayed relatively good responses and were able to guide the varying process variables back to the intended set-point. Hence, it is concluded that is possible to utilise linear methods to control the dynamics of a reactive distillation column. Even so, the disturbances implemented were relatively small-scale and not too large. Therefore, further tuning and changes may have to be made to further improve the tuning of these controllers if this control system is to be implemented on a larger scale.